Form, Materiality, and Symbolism in Non-Arabic Muslim Arts: A Case Study from Indonesian Wayang Performance - Lutfianto, Lutfianto; Junaidi, Junaidi (UIN Sunan Kalijaga Yogyakarta, 2022)
The puppet theater becomes a popular form of cultural expression in the Muslim world, even though wayang performances are not considered a central part of Islamic theology. Wayang performances are seen as having a spiritual significance among Indonesian Muslims for centuries. Such puppet theater incorporates forms, styles, and elements of Islamic spirituality and traditional Javanese cultural practices into its narratives. The article pays attention to the idiosyncratic forms, elements, and meanings of contemporary wayang through the craftsman’s framework. The analysis takes into account the formulation and presentation of the wayang in contemporary Indonesian art, focusing on the creation of “Wayang Kekayon Khalīfah Paraga Umar ibn al-Khaṭṭāb.” This wayang is associated with the figure of 'Umar b. Khaṭṭab (d. 644). Umar is a historical figure who played a significant role in the early history of Islam and is revered for his wisdom and leadership by most Muslims. The discussion argues that the materiality of puppets in the non-Arab Muslim world not only functions as a traditional form of entertainment stimulating the sense of “fun” but also as complex semiotic experiences between a dhalang (wayang puppeteer) and his audiences using signs of two-dimensional buffalo leather and its silhouettes.